Modeling quality of life in patients with rheumatic diseases: the role of pain catastrophizing, fear-avoidance beliefs, physical disability, and depression. Issue 13 (19th June 2018) - Shim, Eun-Jung; Hahm, Bong-Jin; Go, Dong Jin; Lee, Kwang-Min; Noh, Hae Lim; Park, Seung-Hee; Song, Yeong Wook
Abstract: Purpose: To examine factors in the fear-avoidance model, such as pain, pain catastrophizing, fear-avoidance beliefs, physical disability, and depression and their relationships with physical and psychological quality of life in patients with rheumatic diseases. Materials and methods: The data were obtained from 360 patients with rheumatic diseases who completed self-report measures assessing study variables. Structural equation modeling was used to examine the hypothesized relationships among factors specified in the fear-avoidance model predicting physical and psychological quality of life. Results: Final models fit the data well, explaining 96% and 82% of the variance in physical and psychological quality of life, respectively. Higher pain catastrophizing was related to stronger fear-avoidance beliefs that had a direct negative association with physical disability and depression, which, in turn, negatively affected physical quality of life. Pain severity was also directly related to physical disability. Physical disability also affected physical quality of life indirectly through depression. The hypothesized relationships specified in the model were also confirmed for psychological quality of life. However, physical disability had an indirect association with psychological quality of life via depression. Conclusion: The current results underscore the significant role of cognitive, affective, and behavioral factors in perceived physical disability and their mediated detrimental effect on physical and psychological quality of life in patients with rheumatic diseases. Implications for rehabilitation: The fear-avoidance model is applicable to the prediction of quality of life in patients with rheumatic diseases. As pain-catastrophizing and fear-avoidance beliefs are important factors linked to physical disability and depression, intervening these cognitive factors is necessary to improve physical function and depression in patients with rheumatic diseases. Considering the strong association between depression and physical and psychological quality of life, the assessment and treatment of the former should be included in the rehabilitation of patients with rheumatic diseases. Interventions targeting physical function and depression are likely to be effective in terms of improving physical and psychological quality of life in patients with rheumatic diseases.